Enhancing the performance of search engines based heap based data file and hash based indexing file - Jkr Sastry, Dr; Sai Chittibomma, Chandu; Manohara Reddy Alla, Thulasi (International Journal of Engineering and Technology, 2018)
WEB clients use the WEB for searching the content that they are looking for through inputting keywords or snippets as input to the search engines. Search Engines follows a process to collect the content and provide the same as output in terms of URL links. Sometimes enormous time is taken to fetch the content fetched especially when it goes into number of display pages. Locating the content among the number of pages of URLS displayed is complex. Proper indexing method will help in reducing the number of display pages and enhances the seed of processing and result into reducing the size of index space.In this paper a non-clustered indexing method based on hash based indexing and when the data is stored as a heap file is presented that helps the entire search process quite fast requiring very less storage area.Â